The Demand for Urban Mass Transportation - Lave, Charles A. (The Review of Economics and Statistics, 1970)
SOME OF THE FACTORS WHICH INFLUENCE THE COMMUTER'S CHOICE OF MODE ARE EXPLORED BY PROVIDING QUANTITATIVE ESTIMATES OF THE DEGREE OF TRANSIT IMPROVEMENT WHICH WILL BE NECESSARY TO ATTRACT COMMUTERS. THERE IS DEVELOPED AND ESTIMATED A BEHAVIORALLY-ORIENTED MODEL OR MODAL CHOICE. THE TWO MAIN RESULTS WERE: ESTIMATE OF THE VALUE OF TRAVEL TIME TO COMMUTERS (WHICH WAS ESTIMATED AS 42 PER CENT OF THE COMMUTER'S WAGE RATE); AND ESTIMATE OF THE TIME AND COST ELASTICITIES OF CHOICE BETWEEN MODES (WHICH TURNED OUT TO BE RELATIVELY SMALL). UNLESS COMFORT TURNS OUT TO BE A MUCH MORE IMPORTANT FACTOR THAN EITHER TIME OR COST, THE POSSIBILITY FOR ANY SUBSTANTIAL DIVERSION OF AUTO USERS ONTO THE PROPOSED RAPID TRANSIT SYSTEMS DOES NOT APPEAR TO BE VERY GOOD. /AUTHOR/